ANALISIS KEMAMPUAN LITERASI MEDIA BARU MAHASISWA KOMUNIKASI DAN PENYIARAN ISLAM IAIN LANGSA - Samsuar (SYMBOLE, 2025)
Social media is a place that is visited by many young people in various parts of the world. They are free to do anything, one of which is getting information from anywhere, various information scattered on social media can trigger the spread of fake news or often called hoaxes and various other negative things. Therefore, media literacy is needed to support social media activities. According to Art Silverbatt in (Tamburaka, 2016) media literacy is a media awareness movement by the mass media community using a media delivery system approach to media audiences. Media literacy is very much needed to provide knowledge and further cultivate a reading or writing movement so that it can bombard the virtual community to be proficient in receiving false information and other similar things. This paper focuses on discussing how the ability of kpi iain langsa students in media literacy and what are the obstacles to media literacy in kpi iain langsa students. This article is designed with a qualitative research approach, with a research focus using descriptive methods. The results of this study indicate that the mastery of media literacy of kpi students is normal or in the sense that it is quite adequate in literacy, kpi students are able to use the media technically well, they are also able to think critically and can filter incoming information and are able to produce or create content in new media. There are no significant obstacles in the ability of beliterasi to kpi students iain langsa, but only related to technical obstacles.